2016
DOI: 10.1016/j.apcata.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III) porphyrin supported on S and N co-doped graphene quantum dot as an efficient photocatalyst for aerobic oxidation of alcohols under visible light irradiation

Abstract: In this study, we report the synthesis and impressive performance of Fe(III)tetra(4sulfonatophenyl) porphyrins (FeTSPP) supported on S and N co-doped graphene quantum dots (S, N: GQDs) as efficient, recyclable, and noble metal free heterogeneous photocatalyst for the selective aerobic oxidation of alcohols to the corresponding carbonyl compounds. It was found that FeTSPP@S, N: GQDs photocatalyst represents a novel chemical function for efficient visible light catalyzed aerobic alcohol oxidation with good conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 87 publications
1
29
0
Order By: Relevance
“…Additionally, the catalysts are typically supported on solid support, nanoparticles 184 or as quantum dotsdoped with the appropriate metal to promote the transformation. 185 While these materials can be somewhat laborious to prepare, the possibility of repeated recovery and reuse minimizes the impact. To date, oxidations of alcohols to aldehydes, ketone and esters has been demonstrated.…”
Section: Alternatives For Oxidations C-o or C-n Redox Processesmentioning
confidence: 99%
“…Additionally, the catalysts are typically supported on solid support, nanoparticles 184 or as quantum dotsdoped with the appropriate metal to promote the transformation. 185 While these materials can be somewhat laborious to prepare, the possibility of repeated recovery and reuse minimizes the impact. To date, oxidations of alcohols to aldehydes, ketone and esters has been demonstrated.…”
Section: Alternatives For Oxidations C-o or C-n Redox Processesmentioning
confidence: 99%
“…A Z-scheme electron transfer originated from coexistence of p-and ntype conductivity domains in NGO-QDs was proposed to account for the observed photocatalytic activity. In the following studies, GQDs were also used to functionalize the photoactive inorganic and organic materials (semiconductors (SCs) [23][24][25][26][27][28][29][30][31][32][33][34][35][36], polymers [39][40], and dyes [41][42][43][44][45]) for developing advanced nanohybrids with enhanced performances. Specifically, GQDs have been coupled with several SCs including UV-light-responsive TiO2 and ZnO as well as visible-light-responsive CdSe for photo(electro)catalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, In 2016, Mahyari et al . devised an active, reusable, and novel heterogeneous photocatalyst for the aerobic oxidation of several alcohols to the related aldehydes . For this purpose, the authors designed and prepared Fe (III)tetra(4‐sulfonatophenyl)porphyrins (FeTSPP) supported on S and N co‐doped graphene quantum dots (S, N: GQDs).…”
Section: Oxidation Of Alcohols and Arenesmentioning
confidence: 89%
“…[37,38] Accordingly, In 2016, Mahyari et al devised an active, reusable, and novel heterogeneous photocatalyst for the aerobic oxidation of several alcohols to the related aldehydes. [39] For this purpose, the authors designed and prepared Fe (III) tetra(4-sulfonatophenyl)porphyrins (FeTSPP) supported on S and N co-doped graphene quantum dots (S, N: GQDs). The results demonstrated that FeTSPP@S, N: GQDs photocatalyst demonstrate a remarkable catalytic activity for the aerobic alcohol oxidation under the visible light ( Figure 5).…”
Section: Graphene-supported Porphyrinmentioning
confidence: 99%